This was tough. I spent at least 3 minutes (during the exam is not possible)
We can rephrase the stimulus but I see a lot of options to do. Is not straight (at least for me). Ok better to look at the statements
2) this say nothing about \(=\)between the left part of equation and the right part
INSUFF1) square boot sides so we have \((3^x + 3^-x)^2\)\(=\)\(\sqrt{b + 2}^2\)
Now we 'd have \(9^x\) that is, is the same of \(3^2x\) ------->
\(9^x + 9^-x + 2 ( 3^x + 3^-x)\)\(=\) \(b + 2\) ---------> \(9^x + 2 + 9^-x = b + 2\)
In the end \(9^x + 9^-x = b\)
SUFF
A should be the answer Note: \(2 ( 3^x + 3^-x)\) is
zero because we have \(3^ x- x\) . a number power zero is 1 ---> \(2*1 = 2\) for me is more than 600 level